Intra-abdominal hypertension as a risk factor for acute kidney injury in geriatric patients after emergency abdominal surgery - Nataliia Momot; Sergiy Vorotyntsev (Journal of Education, Health and Sport, 2024)
Intra-abdominal hypertension is an often underestimated risk factor for acute kidney injury (AKI). But the values of intra-abdominal pressure (IAP) and abdominal perfusion pressure (APP), which are critical for the development of AKI in elderly patients after urgent abdominal surgery, are still not defined.